Teacher Influence and Student Motivation in Cross-Interest Economics Learning for SDG 4 (Quality Education) - Fransisca Dea Ayu Zagita; Riza Yonisa Kurniawan (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study aims to analyse the partial influence of teachers' roles and student motivation on the decision to choose cross-interest economic programmes among high school students. Method: An explanatory quantitative method was employed to examine the relationship between variables using a questionnaire as an instrument. The sampling technique used saturated sampling, including all tenth-grade students at Petra Christian High School 3 Surabaya. Data analysis was conducted using SEM-PLS with the assistance of WarPPLS software. Results: This research found that the role of teachers has a positive and significant influence on the decision to choose interdisciplinary economics programs, while motivation has no effect. This emphasises the importance of the teacher's role as well as the need for improvements in economics teaching to make it more engaging. Novelty: Contextualising research in the latest location and time is a novelty because learning has changed since the revision of government policy. Teacher training to make economics a flagship subject is also important and urgent today.